Temporary inhibition of dorsal or ventral hippocampus by muscimol: distinct effects on measures of innate anxiety on the elevated plus maze, but similar disruption of contextual fear conditioning - Zhang, Wei-Ning; Bast, Tobias; Yan, Xu; Feldon, Joram (Elsevier, 2013)
Studies in rats, involving hippocampal lesions and hippocampal drug infusions, have implicated the hippocampus in the modulation of anxiety-related behaviors and conditioned fear. The ventral hippocampus is considered to be more important for anxiety- and fear-related behaviors than the dorsal hippocampus. In the present study, we compared the role of dorsal and ventral hippocampus in innate anxiety and classical fear conditioning in Wistar rats, examining the effects of temporary pharmacological inhibition by the GABA-A agonist muscimol (0.5 ug/0.5 ul/side) in the elevated plus maze and on fear conditioning to a tone and the conditioning context. In the elevated plus maze, dorsal and ventral hippocampal muscimol caused distinct behavioral changes. The effects of ventral hippocampal muscimol were consistent with suppression of locomotion, possibly accompanied by anxiolytic effects, whereas the pattern of changes caused by dorsal hippocampal muscimol was consistent with anxiogenic effects. In contrast, dorsal and ventral hippocampal muscimol caused similar effects in the fear conditioning experiments, disrupting contextual, but not tone, fear conditioning.